2015
DOI: 10.1038/jp.2015.128
|View full text |Cite
|
Sign up to set email alerts
|

Can fetal pulmonary artery Doppler indices predict neonatal respiratory distress syndrome?

Abstract: Development of neonatal RDS can be predicted using the MPA At/Et with high sensitivity and specificity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
28
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 23 publications
9
28
1
Order By: Relevance
“…The results of this study suggest that the estimated FMPAP calculated using the formula above, decreases with advancing GA. This finding supports previous reports that show a decreased impedance in the pulmonary vasculature as the fetus approaches term, as well as the potential utility of the formula proposed by Dabestani et al in the estimation of FMPAP [1,2,9,11,20].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results of this study suggest that the estimated FMPAP calculated using the formula above, decreases with advancing GA. This finding supports previous reports that show a decreased impedance in the pulmonary vasculature as the fetus approaches term, as well as the potential utility of the formula proposed by Dabestani et al in the estimation of FMPAP [1,2,9,11,20].…”
Section: Discussionsupporting
confidence: 92%
“…The importance of Doppler as a non-invasive method of estimating the pulmonary artery pressure in neonates and adults has been demonstrated in numerous studies [3][4][5][6][7]. In the fetus, the Doppler evaluation of the main pulmonary artery has been shown to be useful in the analysis of the impedance of such vascular systems and changes in those variables have been demonstrated to correlate with GA, fetal lung maturity and neonatal outcomes [1,2,[8][9][10][11]. Our review of the literature showed a lack of information about fetal main pulmonary artery pressure (FMPAP) and its behavior in regard to GA.…”
Section: Introductionmentioning
confidence: 99%
“…Different from us and the above‐mentioned authors, Ustunyurt et al reported significant decreases in the PA PI and RI at 24 and 48 hours after administration of the first dose of betamethasone ( P = .02 and .01 for PI; P = .001 and .004 for RI, respectively). Similarly, Moety et al also showed that, compared with fetuses who did not develop neonatal RDS, fetuses who developed RDS had a significantly higher PI and RI.…”
Section: Discussionmentioning
confidence: 89%
“…5th, 25th, 50th, 75th, 90th, 95th and 99th Percentile of Pulse -Doppler -Derived Parameters of PSV, PI, AT, ET and AT/ET of the Pulmonary and Aorta in 146 Healthy Fetuses of Singleton Pregnancies According to "Fetal Sex" All of the 5 th to 95 th percentiles are less than the "0.305" cutoff value provided by Moety et al(2).…”
mentioning
confidence: 80%
“…All fetal transabdominal echocardiographic examinations were performed by an experienced pediatric cardiologist using a Medison SonoAce X8 Ultrasound Machine (Samsung Medison Co., Korea) equipped with a C2-8 curved phased array transducer. Pulsed -Doppler sample volume (SV) was placed in the main PA, midway between the pulmonary valve and bifurcation, into right and left PA, according to the technique previously described (Figure 1 and Appendix 1 in Supplementary File) (2).…”
Section: Fetal Echocardiographic Examinationmentioning
confidence: 99%